2013
DOI: 10.1136/heartjnl-2013-303927
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of valve haemodynamics, reverse ventricular remodelling and myocardial fibrosis following transcatheter aortic valve implantation compared to surgical aortic valve replacement: a cardiovascular magnetic resonance study

Abstract: ObjectiveTo compare the effects of transcatheter aortic valve implantation (TAVI) and surgical aortic valve replacement (SAVR) on aortic valve haemodynamics, ventricular reverse remodelling and myocardial fibrosis (MF) by cardiovascular magnetic resonance (CMR) imaging.DesignA 1.5 T CMR scan was performed preoperatively and 6 months postoperatively.SettingUniversity hospitals of Leeds and Leicester, UK.Patients50 (25 TAVI, 25 SAVR; age 77±8 years) high-risk severe symptomatic aortic stenosis (AS) patients.Main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 29 publications
(20 reference statements)
5
65
1
3
Order By: Relevance
“…It is possible that the MF regression is different according to sex, with the more varied distribution n early tendency to regress.. It is also possible that the regression in females is a reflection of the fact that more females underwent trans-catheter rather than surgical valve replacement, as it has previously been suggested that MF regression is seen following TAVR but not SAVR 15 . Failure of MF regression following AVR has been reported previously;…”
Section: Myocardial Fibrosismentioning
confidence: 80%
See 1 more Smart Citation
“…It is possible that the MF regression is different according to sex, with the more varied distribution n early tendency to regress.. It is also possible that the regression in females is a reflection of the fact that more females underwent trans-catheter rather than surgical valve replacement, as it has previously been suggested that MF regression is seen following TAVR but not SAVR 15 . Failure of MF regression following AVR has been reported previously;…”
Section: Myocardial Fibrosismentioning
confidence: 80%
“…CMR imaging is the reference standard for LV mass and volume quantitation, with low intra-observer and inter-study variability. Moreover, sex-related differences in MF may play a key role in any reverse remodeling 15 . This can be accurately quantified non-invasively using the CMR late gadolinium enhancement (LGE) technique.…”
Section: Fibrosis (Mf) May Be Implicated Echocardiographic and Cardimentioning
confidence: 99%
“…Details of the CMR pulse sequence have been previously published [3]. Briefly, CMR was performed pre-procedure (median 1 day, IQR 0 days) and prior to hospital discharge (median 4 days, IQR 1 day) using the same 1.5T scanner (Philips Healthcare, Best, The Netherlands).…”
Section: Cmr Acquisitionmentioning
confidence: 99%
“…Surgical aortic valve replacement (SAVR) and trans-catheter aortic valve implantation (TAVI) result in significant LV mass regression at medium and long term follow up [3,4], with TAVI having a superior mass reduction compared with SAVR at 6 months [3]. TAVI results in an immediate, greater improvement in aortic pressure gradient [5].…”
Section: Introductionmentioning
confidence: 99%
“…Očekuje se da je jedna od odrednica prognoze AS-a fibroza miokarda koja nastaje uslijed dugoročnog preopterećenja pritiska. Fairbairn et al 45 pokazali su da se fibroza miokarda mjerena CMR-om smanjila u razdoblju od 6 mjeseci nakon podvrgnuća TAVI, iako nije primijećen nikakav učinak kod pacijenata koji su bili podvrgnuti kirurškoj zamjeni aortnog zalistka. 150 vessels of intermediate stenosis from 252 patients, FFRCT was better than CCTA for the diagnosis of lesion-specific ischaemia.…”
Section: Ostalounclassified